Cerebral venous thrombosis in Latin America: A critical review of risk factors, clinical and radiological characteristics - Bezerra, Gabriel Marinheiro dos Santos; Cavalcante, Yasmin da Silveira; Matos-Neto, Paulo Roberto; Cavalcante-Neto, Joaquim Francisco; Ponte, Keven Ferreira da; Aguiar de Sousa, Diana; Leal, Paulo Roberto Lacerda; Ribeiro, Espártaco Moraes Lima (Frontiers in Neurology, 2022)
Cerebral venous thrombosis (CVT) is a rare disease that frequently occurs in young women of childbearing age, with variable clinical presentation in regions with limited access to diagnostic imaging or specialized neurological care. In the last decade, there has been an increase in the number of studies on CVT in Latin America, which may contribute to a better epidemiological description of the disease in this region and, consequently, its early diagnosis. Objectives: Our study aims to review the risk factors, clinical and radiological characteristics of CVT in Latin America, being critically compared with data from world literature. Methods: PubMed, ScienceDirect, BVS, and Scopus were searched to identify studies reporting CVT in Latin American countries published up to July of 2022. We excluded case reports and case series reporting < 5 patients later in the final analysis. Results: We identified a total of 3714 studies and 26 qualified for the quantitative analysis, which described 1486 cases of CVT. Headache was the most frequent symptom (82.1%) and the use of oral contraceptives in women was the main risk factor (46.7%). The transverse sinus was the most frequent location of the thrombus (52%). The treatment used most in the acute phase was heparin (88.5%) and oral anticoagulation was widely used at hospital discharge (67.8%). The mortality was low (6.5%), and most patients achieved complete recovery (75.3%). Conclusion: Despite considerable dissimilarities in studies between countries, particularities were identified in the risk factors of CVT in Latin America compared to other regions of the world.